Aplikasi Kosmologi pada Interior Tongkonan (Studi Kasus Interior Tongkonan Di Desa Sadan, Kabupaten Toraja Utara) - Lintu Tulistyantoro, Kevin Samuel Hosen (Intra, 2014)
Cosmology is the understanding of the world. In Toraja culture, the dominant cosmology is field cosmology. Purpose of this research is to analyze how paradigm of Toraja people understand the world, based on the principles of field cosmology that applicated through interior design of Tongkonan. This research aims to examine the practical application of the field cosmology on Tongkonan interior, so it can provide insight and new discourse for practitioners and students of interior design later.Â